ASSESSMENT OF BIRDS ’ FAUNA, OCCURRENCE STATUS, DIVERSITY INDICES AND ECOLOGICAL THREATS AT MANGLA DAM, AJK FROM 2011 TO 2014 - B. N. Khan; Z. Ali (Journal of Animal and Plant Sciences, 2015)
The field surveys of Mangla Dam AJK were conducted to measure its avian diversity between May 2011 and April 2014. The study was undertaken to determine the birds’ fauna occurrence status, diversity indices and ecological threats to their conservation. Point count method was used for data collection. Findings of the research revealed that maximum account of 57892 birds of 188 species belonging to 57 families and representing 17 orders were observed during May 2011to April 2012. A steady decline in birds’ population was noticed while diversity of the order Passeriformes was highest on dam. The Maximum values of diversity indices were also recorded in study year 2011-2012 i.e. Shannon-Weiner 2, Diversity Index (H´) was 3.41; Census Index (CI) was 218/Km Simpson’s Diversity Index (D) was 0.95 and evenness of birds was 0.65. According to ranking of birds occurrence status for the Mangla Dam 15 species were very abundant, 11 were abundant, very common were 41, common were 42, fairly common were 64, uncommon were 5 and 2 were rare. The season wise distribution of bird’s species shown that 71 percent were year around resident, summer breeders were 13 percent, winter migrants were 64 percent and 29 percent were passage migrants. The most dominant species of study area were Common Pochard Aythya ferina (n=5011), Common Coots Fulica atra (n=4782), Little Cormorant Phalacrocorax niger (n=4764), Garganey Anas querquedula (n=3863) Mallard Anas platyrhynchos (n=3841), Northern Shoveler Anas clypeata (n=3743) Tufted Duck Aythya fuligula (n=3393) Northern Pintail Anas acuta (n=3261) and Gadwall Anas strepera (n=2971). The major threats observed including illegal hunting, trapping, unsustainable fisheries practices, deforestation in dam catchment area and water pollution. Mangla Lake, Rawal Lake and Zangi Nawar Lake. The
Keywords: Avian Fauna; Diversity Indices; Ecological Threats; Mangla Dam.